PENDEKATAN DALAM STUDI ISLAM AL-QURAN SEBAGAI KATA TERUCAP DAN KONTRIBUSI ISLAM UNTUK MEMAHAMI KITAB SUCI - Hartono, Hartono (At-Tawazun, Jurnal Ekonomi Syariah, 2020)
Islam, to be precise, Islam (with a small "i") has become a topic of study that continues to develop until now, in the Western world, many universities have even opened Islamic studies classes and are of interest to many circles. This fact is a sign that Islam actually comes in many faces, so that multiple perspectives in understanding Islam are a necessity today. One of them is understanding the Koran in the word dimension.